Initiating Ullmann-like coupling of Br2Py by a semimetal surface - Jinping Hu (Nature Portfolio, 2021)
Abstract Intensive efforts have been devoted to surface Ullmann-like coupling in recent years, due to its appealing success towards on-surface synthesis of tailor-made nanostructures. While attentions were mostly drawn on metallic substrates, however, Ullmann dehalogenation and coupling reaction on semimetal surfaces has been seldom addressed. Herein, we demonstrate the self-assembly of 2, 7-dibromopyrene (Br2Py) and the well controllable dehalogenation reaction of Br2Py on the Bi(111)–Ag substrate with a combination of scanning tunnelling microscopy (STM) and density functional theory calculations (DFT). By elaborately investigating the reaction path and formed organic nanostructures, it is revealed that the pristinely inert bismuth layer supported on the silver substrate can initiate Ullmann-like coupling in a desired manner by getting alloyed with Ag atoms underneath, while side products have not been discovered. By clarifying the pristine nature of Bi–Ag(111) and Ullmann-like reaction mechanisms, our report proposes an ideal template for thoroughly exploring dehalogenative coupling reaction mechanisms with atomic insights and on-surface synthesis of carbon-based architectures.